Music and More Music (XIX): Classical Music (Journal of Parents and Teachers, 2013)
This article talks about Classical music and is the nineteenth article from the series “Music and more Music”. It consists on a brief explanation of this style focusing on its history, social context, musical characteristics and the topics that are more likely to appear. After the introduction, the author proposes a song to work in the classroom by doing an analysis of the lyrics and the music. At the end, there are various activities related to the song that are orientated to work different values in the class. The song that was chosen in this article is the Synphony No.3 by Górecki. The values that can be found in this song are freedom, tolerance, historical consciousness and quest to find the meaning of life.
Keywords: Music; Values; Freedom; Tolerance; Meaning of life; music and education.